Persuasive evidence for electron-nuclear coupling in diluted magnetic colloidal nanoplatelets using optically detected magnetic resonance spectroscopy - Strassberg, Rotem (2020)
The incorporation of magnetic impurities into semiconductor nanocrystals with size confinement promotes enhanced spin exchange interaction between photogenerated carriers and the guest spins. This interaction stimulates new magneto-optical properties with significant advantages for emerging spin-based technologies. Here we observe and elaborate on carrier-guest interactions in magnetically doped colloidal nanoplatelets with the chemical formula CdSe/Cd1-xMn x S, explored by optically detected magnetic resonance and magneto-photoluminescence spectroscopy. The host matrix, with a quasi-type II electronic configuration, introduces a dominant interaction between a photogenerated electron and a magnetic dopant. Furthermore, the data convincingly presents the interaction between an electron and nuclear spins of the doped ions located at neighboring surroundings, with consequent influence on the carrier's spin relaxation time. The nuclear spin contribution by the magnetic dopants in colloidal nanoplatelets is considered here for the first time.